Detoxification of Aflatoxin-Contaminated Maize by Neutral Electrolyzed Oxidizing Water - Jardon Xicotencatl, Samantha; Díaz Torres, Roberto; Marroquín Cardona, Alicia Guadalupe; Villarreal Barajas, Tania; Méndez Albores, Abraham (Molecular Diversity Preservation International, 2015)
Aflatoxins, a group of extremely toxic mycotoxins produced by Aspergillus flavus, A. parasiticus and A. nomius, can occur as natural contaminants of certain agricultural commodities, particularly maize. These toxins have been shown to be hepatotoxic, carcinogenic, mutagenic and cause severe human and animal diseases. The effectiveness of neutral electrolyzed oxidizing water (NEW) on aflatoxin detoxification was investigated in HepG2 cells using several validation methodologies such as the 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide assay, the induction of lipid peroxidation, the oxidative damage by means of glutathione modulation, the Ames test and the alkaline Comet assay. Our results showed that, after the aflatoxin-contaminated maize containing 360 ng/g was soaked in NEW (60 mg/L available chlorine, pH 7.01) during 15 min at room temperature, the aflatoxin content did not decrease as confirmed by the immunoaffinity column and ultra performance liquid chromatography methods. Aflatoxin fluorescence strength of detoxified samples was similar to untreated samples. However, aflatoxin-associated cytotoxicity and OPEN ACCESS Toxins 2015, 7 4295 genotoxicity effects were markedly reduced upon treatment. According to these results, NEW can be effectively used to detoxify aflatoxin-contaminated maize.